Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Medium Gambut yang di Pupuk dengan Limbah Cair Pabrik Kelapa Sawit dan Cendawan Mikoriza Arbuskular - Irwanto Pavrino Aryandri S; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to see the effect of the interaction between palm oil mill effluent and arbuscular mycorrhizal fungi and to obtain oil palm seedlings that meet growth standards even though they are planted on peat medium. This research was carried out at the Experimental Garden of the Faculty of Agriculture, Riau University, Bina Widya Campus km12.5 Simpang Baru Village, Widya District, Pekanbaru City from September 2019 to January 2020. This study used a completely randomized design consisting of of 2 factors. The first factor is the volume of palm oil mill effluent which consists of 4 levels, namely 0 l/seed (control), 0.9 l/seed, 1.8 l/seed and 2.7 l/seed. The second factor was the dose of the arbuscular mycorrhizal fungus which consisted of 4 levels, namely 0 g/seed (control), 5 g/seed, 10 g/seed and 15 g/seed. Parameters observed during the study were nutrient uptake (mg/seed), percentage of mycorrhizal infection (%), increase in height (cm), increase in number of leaves (strands), increase in bulb diameter (cm), root volume (cm3), root crown ratio and dry weight (g). The data obtained from the observations were analyzed statistically with variance, the results of the analysis of variance that had a significant effect were then analyzed further with the Least Significant Difference (BNT) test at the 5% level. The results showed that: (1). The interaction between the application of palm oil mill effluent (LCPKS) and arbuscular mycorrhizal fungi (CMA) on peat medium affected the nutrient uptake parameters (P and K), height increase, leaf number increase, wee diameter increase, root crown ratio and seedling dry weight. Palm oil. Meanwhile, the parameters of mycorrhizal infection percentage and root volume did not show any interaction. (2). Interaction of LCPKS treatment with a volume of 1.8 l/seed and CMA at a dose of 15 g/seed gave good results for the growth of oil palm seedlings. Keywords: Growth, oil palm nursery, peat soil, palm oil mill effluent and arbuscular mycorrhizal fungi